2015
DOI: 10.1108/aaaj-12-2012-1182
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian public sector accounting reforms: dialogic aspirations a step too far?

Abstract: Purpose – Drawing from an interest in the changing Indonesian political and regulatory history, the purpose of this paper is to provide an understanding of the role that accounting reform can play in nurturing, or failing to nurture, a more dialogic form of accounting in a local Indonesian municipality. Design/methodology/approach – To collect the data, the authors undertook a case study of a local municipality and drew from patterns found in Indonesia’s long colonial history. Data were acquired from offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 70 publications
4
66
1
4
Order By: Relevance
“…13 In a recent publication, Harun et al (2015) show that the history of centralization and the culture of apathy and submissiveness in Indonesia inhibit public-sector reforms aiming to strengthen accountability and participation at the local governmental level.…”
Section: Concluding Remarks and Way Forwardmentioning
confidence: 99%
“…13 In a recent publication, Harun et al (2015) show that the history of centralization and the culture of apathy and submissiveness in Indonesia inhibit public-sector reforms aiming to strengthen accountability and participation at the local governmental level.…”
Section: Concluding Remarks and Way Forwardmentioning
confidence: 99%
“…Tools such as Q methodology (Byrch et al, 2015), futures thinking through Utopian visioning (Atkins et al, 2015), and scenarios methods are examples of useful technologies to identify people's self-interpretations and future desires but they are insufficient on their own (Glynos and Howarth, 2007, chapter 2). As Harun et al (2015) demonstrate, actors' understandings must be placed within their historical, cultural and socio-political contexts [6] for, as Modell (2015, pp. XX) observes, reflexive agency may vary according to structural conditions in which actors are embedded and their personal characteristics [7].…”
Section: 5mentioning
confidence: 99%
“…Byrch et al (2015) note how the diverse perspectives on sustainability, the contested nature of the domain, and the disinterest of those in power in listening to or debating with alternative voices stymies possibilities for agonistic dialogue and debate. Célérier and Cuenca (2015) and Harun et al (2015) similarly found facilitating pluralism and democratic participatory governance through new forms of accounting problematic, not least in developing countries. However, some change is possible.…”
mentioning
confidence: 99%
See 2 more Smart Citations